Impact of antibiotic-induced dysbiosis in childhood: Effects on immunological development and the risk of chronic diseases such as asthma, allergies, and obesity - Sarasti Espejo, Juan José; Guayasamín Calispa, Nathalye Stepfanye; Bedoya Hidalgo, Emily Sofía; Herrera Jaramillo, Ana Paula (RECIMUNDO, 2025)
Antibiotic-induced dysbiosis in childhood has significant consequences for immunological development and is associated with an increased risk of chronic diseases such as asthma, allergies, and obesity. Antibiotics alter the composition and diversity of the gut microbiome, which is crucial for the maturation of the immune system. This early alteration can affect local and systemic immunity, including the gut-lung axis. An exhaustive review of the scientific literature published in databases such as PubMed, Scopus, and Web of Science over the last 5 years was conducted. Search terms included combinations of keywords such as "dysbiosis," "antibiotics," "childhood," "immunological development," "asthma," "allergies," "obesity," and "chronic diseases." Observational studies, clinical trials, and systematic reviews that evaluated the association between antibiotic exposure in childhood, the resulting dysbiosis, and the risk of developing chronic diseases were included. Antibiotic-induced dysbiosis in childhood alters immunological development and increases the risk of asthma, allergies, and obesity. A healthy infant microbiome, crucial for immunity, is affected by antibiotics, reducing its diversity. This early dysbiosis is linked to chronic diseases. To mitigate this, rational antibiotic use, dietary modulation with prebiotics, the use of probiotics/symbiotics, and the investigation of antibiotic alternatives are recommended. An integrated approach is key for healthy immunological development and the prevention of chronic diseases.